Ceramah Literasi Keuangan di Siswa Magang SMK di Lingkungan IBI Kosgoro - Faisal, Andri; Basuki, Rezi Nanda; Muphimin, Muphimin (Prisani Cendekia, 2024)
This community service activity aims to promote financial literacy within the community. It is based on the low interest in saving among Indonesian citizens and the limited understanding of financial literacy, particularly at the high school level (both SMA and SMK). This lack of interest in saving poses a future problem as individuals will face significant life challenges, including financial difficulties. They will need to address pressing issues such as housing and employment.Many students overlook financial literacy education because it is not part of the curriculum in most secondary schools in Indonesia. Consequently, their knowledge of financial literacy remains inadequate. This issue not only burdens individuals and families but also places a strain on the country. A decline in societal welfare compels the government to provide support or subsidies for those below the welfare threshold. Recognizing the importance of this matter, the government, through the Financial Services Authority (OJK), has initiated programs to promote financial literacy to the public.Based on this context, this community service program targets high school (SMA) and vocational school (SMK) students, who are presumed to have low levels of financial literacy. Using a lecture method, the program introduces new knowledge to help students understand the concept of financial literacy. Each aspect of financial definitions is thoroughly explained to ensure comprehension. Financial literacy is a novel concept for them and is expected to benefit them in the future. As a result, they begin to understand financial management and develop a habit of saving for the future. To ensure they know about financial literacy in the lecture, the lecturer will ask them questions. This is to ensure they are able to master financial literacy. Female participants were able to answer that they had a financial goal to buy a house. They are clear about this knowledge and they know it is not easy. Therefore they save to achieve these financial goals.